A Current Overview of the Biological Effects of Combined Space Environmental Factors in Mammals - Xu, Ying; Pei, Weiwei; Hu, Wentao (Frontiers in Cell and Developmental Biology, 2022)
Space environmental factors include microgravity, space radiation, hypomagnetic field, circadian rhythm changes, and so on, which pose lots of adverse effects on the safety and health of astronauts during deep space exploration missions. However, most of the current ground-based studies focused on single-factor biological effects. In order to better understand the biological effects of space environment and the underlying mechanisms and promote the manned space exploration, it is necessary to deeply study the compound biological effects of space environmental factors. This paper summarizes the latest research progress on the compound biological effects of various space environmental factors in order to provide new directions for further exploring the health effects of space environmental factors and the underlying mechanisms, in hope of providing reference for the diagnosis and treatment of diseases induced by space environment.